Fucus vesiculosus L. - Preston, Roxana; Seppä, Perttu; SchagerstrÖm, Ellen; Blomster, Jaanika (Zenodo, 2022)
4.3 Colonisation and demographic history of F. vesiculosus in the Baltic Sea The distribution of mitochondrial haplotypes in the Baltic Sea and the Atlantic Ocean suggests that a single haplotype colonised the Baltic from the Atlantic, and became increasingly geographically and reproductively isolated from the parental populations. Current unique mitochondrial diversity in the Baltic Sea compared to the founding North Atlantic populations can then be explained by novel mutations, and subsequent directional selection and genetic drift. The findings of a single mtDNA PR-IGS haplotype corresponding with our putative ancestral haplotype along the Scandinavian coastline (Coyer et al. 2011a) as well as the analogous demographic characteristics of another recently colonized F. vesiculosus population in North America (Muhlin and Brawley 2009) supports this assumption. Hence, the observed level of genetic variation within the Baltic Sea appears a result of recent divergence, rather than post-colonisation reduction of variation within the Baltic Sea population. Despite the well-documented population declines and subsequent recovery of attached F. vesiculosus within the Baltic Sea, the data showed no solid indications of population bottlenecks or recent population expansion. Recovery is often localised, for example within the S and SW Finnish archipelagos, particularly around the Hanko peninsula (Kangas and Niemi 1985; Rinne and Salovius-Laurén 2020; von Wachenfeldt et al. 1986) and our sampling sites at Seili (Rönnberg et al. 1985). However, many other sites are yet to recover (Rinne and Salovius-Laurén 2020; Snickars et al. 2014; Vahteri and Vuorinen 2016). It is therefore possible that declines and recovery may not have been extreme enough, having only a limited effect on the genetic diversity, and thus the bottleneck signal could not be detected. Furthermore, the limited genetic variation among our samples effectively homogenises the population. Mitochondrial barcode sequencing lacks the resolution to adequately ...